Adsorption of As(III) and As(V) in groundwater by Fe-Mn binary oxide-impregnated granular activated carbon (IMIGAC) - Ryu, So-Ri; Jeon, Eun-Ki; Yang, Jung-Seok; Baek, Kitae (ELSEVIER SCIENCE BV, 2017)
Iron oxide and manganese oxide are well-known sinks and oxidants for As(V) and As(III), respectively. In this study, iron- and manganese-impregnated granular activated carbon (IMIGAC) was synthesized to remove arsenic from aqueous streams. The characterization of IMIGAC shows that Fe-Mn binary oxides are well impregnated into the carbon. The adsorption kinetics and isotherms show that this material effectively removes both As(III) and As(V) without pre-oxidation. The kinetics appear to be pseudo-second order, and the rate-limiting step is determined to be intra-particle diffusion due to the porous structure of the carbon. The isotherm shows that the adsorption capacities for As(III) and As(V) are 18.4 mg/g and 16.0 mg/g at 293 K, respectively. The negative Gibbs free energy change indicates that the reaction is spontaneous. Speciation analysis shows that As(III) is adsorbed onto IMIGAC and then slowly oxidizes to As(V). Based on the experimental results, we conclude that the synthesized IMIGAC can be used to remove As(III) and As(V) from groundwater to yield potable water. (C) 2017 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: AQUEOUS-SOLUTION; ARSENIC(III) SORPTION; DRINKING-WATER; REMOVAL; ADSORBENTS; MANGANESE; EQUILIBRIUM; MECHANISM; BEHAVIOR; KINETICS